2014
DOI: 10.5306/wjco.v5.i3.546
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic lobular carcinoma in situ of the breast: Can the evidence guide practice?

Abstract: The clinical significance of pleomorphic lobular carcinoma in situ (PLCIS) is a subject of controversy. As a consequence, there is a risk of providing inconsistent management to patients presenting with PLCIS. This review aims to establish whether the current guidelines for the management of PLCIS are consistent with current evidence. A systematic electronic search was performed to identify all English language articles regarding PLCIS management. The data was analysed, specifically looking at: incidence of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…11 Due to these pathologic similarities, it has been suggested that management of PLCIS should mirror that of DCIS rather than CLCIS, including excision to clear surgical margins with or without adjuvant postlumpectomy radiation and endocrine therapy. 1215 The risk of concurrent invasive disease, or upgrading, at excision has ranged in prior studies from 0 to 65 %. 9,12 Following excision, ipsilateral recurrence of PLCIS or of invasive breast cancer has been estimated at 3.8–19.4 %, suggesting that PLCIS may represent a precursor lesion to invasive cancer rather than a marker for increased breast cancer risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 Due to these pathologic similarities, it has been suggested that management of PLCIS should mirror that of DCIS rather than CLCIS, including excision to clear surgical margins with or without adjuvant postlumpectomy radiation and endocrine therapy. 1215 The risk of concurrent invasive disease, or upgrading, at excision has ranged in prior studies from 0 to 65 %. 9,12 Following excision, ipsilateral recurrence of PLCIS or of invasive breast cancer has been estimated at 3.8–19.4 %, suggesting that PLCIS may represent a precursor lesion to invasive cancer rather than a marker for increased breast cancer risk.…”
mentioning
confidence: 99%
“…1215 The risk of concurrent invasive disease, or upgrading, at excision has ranged in prior studies from 0 to 65 %. 9,12 Following excision, ipsilateral recurrence of PLCIS or of invasive breast cancer has been estimated at 3.8–19.4 %, suggesting that PLCIS may represent a precursor lesion to invasive cancer rather than a marker for increased breast cancer risk. 12,16 …”
mentioning
confidence: 99%
“…However, it has long been noted that unlike CLCIS, PLCIS may be frequently associated with invasive disease and has more aggressive course (4,9). PLCIS is considered to be a precursor of invasive disease rather than a marker of increased risk like CLCIS.…”
Section: Plcismentioning
confidence: 99%
“…Further articles were identified by manual search through the references in previous reviews and studies (3,4). …”
Section: Introductionmentioning
confidence: 99%
“…Pleomorphic LCIS is linked to a higher risk of invasive cancer and is often treated as though it is a cancer precursor. 50 The strongest evidence that LCIS is more of a risk indicator than a direct cancer precursor comes from registry-based studies. One study of women diagnosed with LCIS from 1973 to 1998 and treated with BCS found that 7% of women developed invasive breast cancer within 10 years, with the increased risk of invasive disease equally distributed between both breasts.…”
Section: What Is Lcis?mentioning
confidence: 99%